Queervertising: An empowerment tool for the gay men and lesbian community. - Iglesias-Sánchez, Patricia Pilar; Jambrino-Maldonado, Carmen; De-las-Heras-Pedrosa, Carlos; Díaz Tendero, Rafael (F1000Research, 2023)
Background: Today’s society clams to be more inclusive, but there has been a lack of practical examination of this area. This study analyses how advertising and society interact and evolve in parallel, with advertising seeking to balance more traditional representations – in accordance with the Mirror Theory – with mainstreaming, which can influence social change. In this case, analysis is focused on the homosexual community. Methods: A content analysis of audiovisual advertising in Spain from the 1960s to 2021 is carried out in addition to a review of historical milestones and legislation. Results: The results evidence the transformation of advertising. The main findings show a shift from the total invisibility of the gay men and lesbian community in the 1960s to effective and respectful integration today. Conclusions: Queervertising is proposed as a new theoretical concept as the result of gender and sexual diversity being identified in advertising over time. The inclusion of gay men and lesbians in advertising is a current trend that, moreover, offers a challenge for brands. Although this turnaround in advertising creativity should be highlighted and recognized as being to some extent responsible for changes and social evolution, the commercial messages which are found today are still not always disruptive or excessively explicit, in order to avoid some rejection by audiences.
Keywords: Publicidad; Homosexuales; Lesbianas; Marcas (Marketing); Queer; Advertising; Gay men and lesbians’ community; LGBTIQ+; Gender identity; Brands